Management package for anthracnose and white mold in Jatropha curcas, a biofuel yielding tree species - and L.C. TIPPESHI, V. SURYANARAYANA*, PRADEEP RATHOD (Indian Phytopathology, 2012)
Common field management package for anthracnose and white mold diseases of Jatropha curcas with integration of fungicides and plant extracts was developed. Sequential sprays of Mancozeb (0.2%) followed by Prosopis juliflora leaf extract (10%) and third with Mancozeb (0.2%) controlled both diseases very efficiently. The periodical successive reduction in rate of disease development (‘r’) from 15 days of first spray to 15 days of third spray was 0.0015 to 0.0001 for white mold, whereas for anthracnose, ‘r’ was 0.0017 to 0.0003 over control. Net return/ha was also high, Rs. 11,701.40 in white mold and Rs. 8,933.90 in anthracnose management. Even though cost-benefit ratio was lower (1:11.4) than the treatment (0.2% mancozeb followed by 10% Prosopis leaf extract) [1:16.2], it was considered as the most effective integrated disease management by considering high net return and low ‘r’ value.